PENGARUH HARGA, IKLAN DAN KUALITAS PELAYANAN TERHADAP KEPUTUSAN PEMBELIAN PELUMAS PADA PT JUMBO POWER INTERNATIONAL BATAM - Robert Lee; Winda Evyanto (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
This study tries to determine whether price, advertising, and service quality have a partial or simultaneous impact on purchasing decisions at PT Jumbo Power International Batam. 3,670 people constitute the study population, all of whom are consumers. 150 respondents were taken as a sample of 150 for this investigation. The saturated sampling technique was used in this work as a sampling technique. This study employs a questionnaire as one of its data collection methods. SPSS 25 program was used to process this data. Quantitative research methodology was used. The results showed that the price showed a t-count value of -6700 <97612. has a negative and significant effect on price on purchasing decisions at PT Jumbo Power International Batam, advertisements show a t-count value of 10,155 <97612 a beneficial and important impact on consumer decisions at PT Jumbo Power International Batam, and service quality with a t-count value of 4,084 <97612 has a positive and significant effect on purchasing decisions at PT Jumbo Power International Batam. price, advertising, and service quality all have a simultaneous, positive and significant effect on purchasing decisions at PT Jumbo Power International Batam to buy a product or service. with the calculated F value is 51.675 > 3.060.